EANM practice guideline/SNMMI procedure standard for dopaminergic imaging in Parkinsonian syndromes 1.0 - Morbelli, Silvia; Esposito, Giuseppe; Arbizu, Javier; Barthel, Henryk; Boellaard, Ronald; Bohnen, Nico I.; Brooks, David J; Darcourt, Jacques; Dickson, John C.; Douglas, David; Drzezga, Alexander; Dubroff, Jacob; et al. (European journal of nuclear medicine and molecular imaging, 2020)
Purpose This joint practice guideline or procedure standard was developed collaboratively by the European Association of Nuclear Medicine (EANM) and the Society of Nuclear Medicine and Molecular Imaging (SNMMI). The goal of this guideline is to assist nuclear medicine practitioners in recommending, performing, interpreting, and reporting the results of dopaminergic imaging in parkinsonian syndromes. Methods Currently nuclear medicine investigations can assess both presynaptic and postsynaptic function of dopaminergic synapses. To date both EANM and SNMMI have published procedural guidelines for dopamine transporter imaging with single photon emission computed tomography (SPECT) (in 2009 and 2011, respectively). An EANM guideline for D2 SPECT imaging is also available (2009). Since the publication of these previous guidelines, new lines of evidence have been made available on semiquantification, harmonization, comparison with normal datasets, and longitudinal analyses of dopamine transporter imaging with SPECT. Similarly, details on acquisition protocols and simplified quantification methods are now available for dopamine transporter imaging with PET, including recently developed fluorinated tracers. Finally, [ 18 F]fluorodopa PET is now used in some centers for the differential diagnosis of parkinsonism, although procedural guidelines aiming to define standard procedures for [ 18 F]fluorodopa imaging in this setting are still lacking. Conclusion All these emerging issues are addressed in the present procedural guidelines for dopaminergic imaging in parkinsonian syndromes.